Enhanced plasmon-driven photoelectrocatalytic methanol oxidation on Au decorated α-Fe2O3 nanotube arrays. Issue 69 (10th July 2018) - Zheng, Bang-Feng; Ouyang, Ting; Wang, Zhu; Long, Jianyou; Chen, Yibo; Liu, Zhao-Qing
Abstract : Highly ordered, porous α-Fe2 O3 /Au nanotube arrays (NTAs) were successfully synthesized through a facile approach. Abstract : Highly ordered, porous α-Fe2 O3 /Au nanotube arrays (NTAs) were successfully synthesized through a facile approach. Benefitting from the plasmonic effect, and unique aligned and porous structural features, the α-Fe2 O3 /Au NTAs offer efficient and stable operation and exhibit a significantly enhanced catalytic activity for photoelectrochemical methanol oxidation with a faradaic efficiency of 79.23%.